Description of Pella sichuanensis sp. n. (Coleoptera: Staphylinidae: Aleocharinae) from Micang Mountain, Sichuan, China - Zheng, Dan-Lin; Zhao, Mei-Jun (Zootaxa, 2014)
Pella sichuanensis Zheng & Zhao, sp. n. of the P. cognata group is described, illustrated, and distinguished from similar congeners.